Local strategic networks in the software industry: an empirical analysis of the value continuum. (6th January 2010) - Hock, Michael; Ringle, Christian M.
This paper explores long-term partnership benefits of local strategic alliances in knowledge-intensive industries. A structural model of the value continuum is formulated and tested on small and mid-size enterprises in the software industry. Partial least squares path analysis is used to investigate the cause?effect relationships between the foundation values – efficiency and effectiveness – and the innovation value. The results show that the innovation value of localised inter-firm networks originates from costs savings and quality improvements. Conversely, alliance-induced 'speed' benefits (measured by the R&D process's acceleration), which improve flexibility and/or shorten delivery time, have no significant impact on market-based performance. An alliance's time-related benefits may be important to maintain competitive parity, but they do not significantly support competitive advantage, market development and market penetration. Instead, value is created via, for example, an exchange of tacit knowledge and a reduction in transaction costs, and particularly by a reduction in customer service costs.